Internet addiction and its associated factors among school-going adolescents in Malaysia - Muhd Hafizuddin Taufik Ramli,; Muhammad Solihin Rezali,; Nik Adilah Shahein,; Norhafizah Sahril,; Chan, Ying Ying; Nor’ Ain Ab Wahab,; Mohd Shaiful Azlan Kassim, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Internet usage has changed the way adolescents socialize. This study aims to determine the determinants of internet addiction among school-going adolescents in Malaysia. This study was a cross-sectional study involving 27,455 school-going adolescents from 212 selected schools in Malaysia, as part of the 2017 National Health and Morbidity Survey that implemented a two-stage stratified cluster sampling design. Data collection via a self-administered questionnaire was conducted from March till May 2017. Overall, 8,049 (29.0%) school-going adolescents had internet addiction. Internet addiction was positively associated with male (odds ratio, OR [95% confidence interval, CI] = 1.20 [1.08,1.34]) compared to female, Chinese ethnicity (1.67 [1.12,2.48]) compared to other ethnicity, feeling loneliness (1.37 [1.20,1.57]) compared to never feel lonely, unable to sleep due to worrying of something (1.40 [1.17,1.67]) compared to able to sleep, insufficient parental supervision (1.30 [1.14,1.48]) compared to sufficient parental supervision, depression (1.67 [1.48,1.89]) compared to no depression, anxiety (2.12 [1.95,2.30]) compared to no anxiety and stress (2.26 [1.96,2.61]) compared to no stress. The odds of having internet addiction increase from Form 2 (1.51 [1.28,1.78]), Form 3 (2.37 [2.01,2.80]), Form 4 (2.60 [1.76,3.85]) to Form 5 adolescents (2.96 [1.98,4.41]) compared to Form 1 adolescents. Our results suggest that being a male, of Chinese ethnicity, higher form level, feeling loneliness, unable to sleep due to worrying of something, insufficient parental supervision, depression, anxiety and stress were positively associated with internet addiction among school-going adolescents.